Summer Mortality Syndrome Affecting Cultured European Seabass at Kafrelsheikh Province, Egypt - Ali, Nadia Gabr; El-Nokrashy, Asmaa Mahmoud; Gouda, Mofeed Yousef; Aboyadak, Ibrahim Mohamed (Frontiers in Marine Science, 2021)
The present work conducted to investigate the causes of summer mortality syndrome affecting cultured European seabass (Dicentrarchus labrax) through examining physiochemical farm water characteristics, automated biochemical identification of the bacterial pathogens isolated from diseased fish, experimental infection of seabass fingerlings with the recovered bacterial isolates and studying the effect of water temperature on stress biomarkers and disease severity. The studied water parameters were normal, except ammonia was higher than the acceptable value and dissolved oxygen was lower than the normal value. Sixty-two bacterial isolate recovered from the moribund fish isolates were identified by VITEK 2 automated biochemical identification system as 31 Vibrio fluvialis, 23 Pseudomonas aeruginosa and 8 Staphylococcus aureus. The calculated LD50 of Vibrio fluvialis, Pseudomonas aeruginosa and Staphylococcus aureus for D. labrax fingerlings were 4.67 × 107, 2.37 × 106 and 1.38 × 107, respectively. Water temperature have directly affects disease severity as the mortality rate was 44.44, 50, 66.66, and 83.33% for fish maintained at 27, 30, 33, and 36 °C after bacterial challenge with Vibrio fluvialis. Stress biomarkers in fish blood as plasma cortisol, superoxide dismutase, catalase and malondialdehyde were significantly increased when the water temperature exceeds 30 °C. The experimentally infected fish are showed similar clinical signs and postmortem lesions appeared on naturally diseased fish with no line of demarcation between different pathogens. Antibiogram test indicated that florfenicol was the most effective antibiotic against all recovered bacterial isolates while all isolates resisted sulfamethoxazole-trimethoprim. Massive degenerative changes observed in the hepatopancreas, posterior kidney and gill tissues of experimentally infected fish.